1974
DOI: 10.2172/4214460
|View full text |Cite
|
Sign up to set email alerts
|

Environmental monitoring at the Lawrence Livermore Laboratory. 1974 annual report

Abstract: Monitoring Data-Collection, Analysis, and Evaluation 4 Radioactive Monitoring 4 Airborne Radioactivity 4 Radioactivity in Soil 8 Radioactivity in Sewage JJ Radioactivity in Water ji Radioactivity in Vegetation , 13 Radioactivity in Milk 13 Environmental Radiation Measurements 15 Non-Radioactive Monitoring 15 Airborne Beryllium 15 Heavy Metals Released to Livermore Sanitary Sewer 17 Physical and Chemical Analysis of LLL Sewage 17 Environmental Impact of LLL Effluents 17 Radioactive Airborne Effluents 17 Radioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These studies have consistently shown that the concentrations of radionuclides in local soils are below levels of health concern. Gudiksen et al 1973Gudiksen et al 1973 Radionuclides in San Joaquin Valley soil Soil study of southeast quadrant of Livermore site Silver et al 1975Silver et al 1976 Evaluation of the Use of Sludge Containing Plutonium as a Soil Conditioner for Food Crops Myers et al 1976Myers et al 1977 Sediments from LLNL to the San Francisco Bay Silver et al 1978Silver et al 1980 Plutonium in soils downwind of the Livermore site Toy et al 1981Toy et al 1990 195 samples taken in southeast quadrant for study Gallegos et al 1992 1991 Drainage channels and storm drains studied Gallegos 1991 1993 EPA studies southeast quadrant Gallegos et al 1994Gallegos et al 1993 Historic data reviewed Gallegos 1993 1995 LLNL, EPA, andDHS …”
Section: -12 2005 Llnl Environmental Reportmentioning
confidence: 99%
“…These studies have consistently shown that the concentrations of radionuclides in local soils are below levels of health concern. Gudiksen et al 1973Gudiksen et al 1973 Radionuclides in San Joaquin Valley soil Soil study of southeast quadrant of Livermore site Silver et al 1975Silver et al 1976 Evaluation of the Use of Sludge Containing Plutonium as a Soil Conditioner for Food Crops Myers et al 1976Myers et al 1977 Sediments from LLNL to the San Francisco Bay Silver et al 1978Silver et al 1980 Plutonium in soils downwind of the Livermore site Toy et al 1981Toy et al 1990 195 samples taken in southeast quadrant for study Gallegos et al 1992 1991 Drainage channels and storm drains studied Gallegos 1991 1993 EPA studies southeast quadrant Gallegos et al 1994Gallegos et al 1993 Historic data reviewed Gallegos 1993 1995 LLNL, EPA, andDHS …”
Section: -12 2005 Llnl Environmental Reportmentioning
confidence: 99%
“…LLNL's first use of these dose-rate formulas in our environmental annual reports is described by Silver et al (1980).…”
Section: Radiation Unitsmentioning
confidence: 99%
“…Silver et al, 1975Silver et al, 1975 LLNL publishes "Evaluation of the Use of Sludge Containing Plutonium as a Soil Conditioner for Food Crops." Sewer sludge from LWRP containing about 2.8 pCi of Pu-239 per gram of sludge used.…”
mentioning
confidence: 99%